Resiliencia y memorias en Perú durante la pandemia - Romio, Silvia (2022)
Peru is one of the countries most affected by the Covid-19 pandemic, where the health crisis quickly provoked a serious socio-economic and political crisis. The fragile Peruvian state was unable to build an effective response to this multifaceted crisis, in this context, we defend the hypothesis that forms of affectivity, solidarity, memory and collective resilience related to the recent past (1980-1990) were reactivated in many rural and urban communities of the country. Based on a qualitative methodology, this article questions the role that the collective memory played in reactivating historical forms of community resilience at the local level. Based on three empirical cases (the rondas campesinas, the Covid commandos and the ollas comunes), we analyze how the memories of past violence and crises, as well as the responses to them, have offered original tools in certain communities to elaborate effective responses of resilience during the first months of the global pandemic. In this sense, we reflect and draw attention to the potential of setting up agency and resilience based on collective memory, which is framed is by the diversity of the cultural and local experiences.